2021
DOI: 10.23910/1.2021.2189d
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Use of Herbicide and Weed Mulch with Closer Spacing for Weed Management in Dry Direct Seeded Rice

Abstract: The field experiments were conducted during the wet season of 2015 and 2016 (June to October) at Agricultural Farm, Institute of Agriculture, Visva-Bharati, Sriniketan, India to study the impact of integrated use of weed mulch and herbicide with closer spacing on weed growth and yield of direct seeded dry sown rice (Oryza sativa L.) cultivar MTU 1010. The experiment consisted of twelve treatments involving sole or integrated application of pre-emergence herbicide pendimethalin, mulching with water hyacinth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Currently, the JPS has begun to be developed by farmers and provides higher rice yield than the TPS by increasing the crop yield to decline in the direct seed planting system (Malik et al, 2021). It was quite clear that the presence of weeds greatly reduced rice yields in rice fields.…”
Section: Advantages Of Jarwo Planting Systemmentioning
confidence: 99%
“…Currently, the JPS has begun to be developed by farmers and provides higher rice yield than the TPS by increasing the crop yield to decline in the direct seed planting system (Malik et al, 2021). It was quite clear that the presence of weeds greatly reduced rice yields in rice fields.…”
Section: Advantages Of Jarwo Planting Systemmentioning
confidence: 99%
“…For effective weed management, improved weed control practices that include chemical weed control with newer formulations and herbicide mixtures and integrated cultivation need to be developed and refined" [6]. Malik et al [5] reported "57% losses respectively due to weeds in rice in India. An integrated approach is required for addressing these issues regarding to soil water-plant-nutrient management at the plant rooting zone.…”
Section: Introductionmentioning
confidence: 99%